d^2y/dx^2-2tanxdy/dx+3y=2secx given that y=sinx is a solution of associated homogeneous equation
y''-2tan(x)y'+3y=2/sec(x) (1)
y=sin(x),y'=cos(x),y''=-sin(x)
y"-2tan(x)y'+3y=-sin(x)-2tan(x)cos(x)+3sin(x)=0
Really, y=sinx is a solution of associated homogeneous equation
y"-2tan(x)y'+3y=0.
Let's find the second solution y2(x) of the homogeneous equation in the form
y(x)=p(x)sin(x)
y'=p'sin(x)+pcos(x)
y''=p''sin(x)+2p'cos(x)-psin(x)
p''sin(x)+2p'cos(x)-psin(x)-2tan(x)(p'sin(x)+pcos(x))+3psin(x)=0
p''sin(x)+2p'cos(x)-psin(x)-2p'sin2(x)/cos(x)-2psin(x)+3psin(x)=0
p''sin(x)+2p'cos(x)-2p'sin2(x)/cos(x)=0
z=p'
z'sin(x)+2zcos(x)-2zsin22(x)/cos(x)=0
z'sin(x)=-2zcos(2x)/cos(x)
dz/z=-2cos(2x)/(cos(x)sin(x))dx
dz/z=-4cos(2x)/sin(2x)dx
"\\int" dz/z=-4"\\int"cos(2x)/sin(2x)dx
ln|z|=-2ln|sin(2x)|+C1
z=C2/sin2(2x)
p'=C2/sin2(2x)
p(x)=-C2cot(2x)/2
Let C2=-4
p(x)=2cot(2x)
y(x)=2cot(2x)sin(x)
y(x)=2cos(2x)sin(x)/sin(2x)
y(x)=2cos(2x)sin(x)/(2sin(x)cos(x))
y(x)=cos(2x)/cos(x)
So,
y2(x)=cos(2x)/cos(x)
The general solution of the homogeneous equation has the form
y(x)=C1sin(x)+C2cos(2x)/cos(x)
The equation (1) can be transform into standart form using the substitution
ln(y)=ln(z)-1/2"\\int"(-2tan(x))dx
ln(y)=ln(z)-ln(cos(x))
y=z/cos(x)
z=cos(x)y
z'=-sin(x)y+cos(x)y'
z''=-cos(x)y-2sin(x)y'+cos(x)y''
cos(x)(y"-2tan(x)y'+3y)=cos(x)y''-2sin(x)y'+3cos(x)y=z''+4z
Multiplying the equation (1) by cos(x) we obtain the equation
z''+4z=2
We will seek a particular solution in the form
z=A
4A=2
A=1/2
zp(x)=1/2
yp(x)=1/(2cos(x))
The general solution of the equation (1) has the form
y(x)=C1sin(x)+C2cos(2x)/cos(x)+1/(2cos(x))
Comments
Leave a comment